Detection of Cryptosporidium parvum Oocysts on Fresh Produce Using DNA Aptamers - Iqbal, Asma; Labib, Mahmoud; Muharemagic, Darija; Sattar, Syed; Dixon, Brent R.; Berezovski, Maxim V. (PLOS ONE, 2015)
There are currently no standard methods for the detection of Cryptosporidium spp., or other protozoan parasites, in foods, and existing methods are often inadequate, with low and variable recovery efficiencies. Food testing is difficult due to the low concentrations of parasites, the difficulty in eluting parasites from some foods, the lack of enrichment methods, and the presence of PCR inhibitors. The main objectives of the present study were to obtain DNA aptamers binding to the oocyst wall of C. parvum, and to use the aptamers to detect the presence of this parasite in foods. DNA aptamers were selected against C. parvum oocysts using SELEX (Systematic Evolution of Ligands by EXponential enrichment). Ten rounds of selection led to the discovery of 14 aptamer clones with high affinities for C. parvum oocysts. For detecting parasite-bound aptamers, a simple electrochemical sensor was employed, which used a gold nanoparticle-modified screen-printed carbon electrode. This aptasensor was fabricated by self-assembling a hybrid of a thiolated ssDNA primer and the anti- C. parvum aptamer. Square wave voltammetry was employed to quantitate C. parvum in the range of 150 to 800 oocysts, with a detection limit of approximately 100 oocysts. The high sensitivity and specificity of the developed aptasensor suggests that this novel method is very promising for the detection and identification of C. parvum oocysts on spiked fresh fruits, as compared to conventional methods such as microscopy and PCR.